Edukasi Gizi Seimbang melalui Leaflet untuk Meningkatkan Pengetahuan Ibu Rumah Tangga - Daiva Alifia; Andi Muh Asrul Irawan (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2026)
Abstract - The problem faced by the community in Mattiro Ujung Village, Kapoposang Island, is the low level of knowledge and attitude among housewives regarding the importance of balanced nutrition. This community service activity aimed to improve the knowledge and attitudes of housewives through nutrition education using balanced nutrition leaflets. The activity was conducted on July 18–19, 2025, with 15 housewives participating. The implementation methods included socialization, pre-test, delivery of materials through interactive lectures using leaflets, group discussions, and post-test. The results showed a significant increase in participants' knowledge after the education was delivered, as seen from the comparison of pre-test and post-test scores. The average knowledge score increased from 4.73 to 7.40 with a significance value of p = 0.001. These findings indicate that the leaflet was effective as an educational tool, especially in island areas with limited access to digital information. This educational activity not only improved participants' understanding but also encouraged a positive shift in attitudes toward adopting balanced nutrition practices within households. The use of printed educational media proved to be a simple, accessible, and impactful approach in promoting better family nutrition awareness in remote coastal communities.   Keyword: Balanced Nutrition, Housewives, Leaflet Media   Abstrak - Permasalahan mitra di Desa Mattiro Ujung, Pulau Kapoposang, yaitu masih rendahnya pengetahuan dan sikap ibu rumah tangga terhadap pentingnya gizi seimbang, menjadi latar belakang pelaksanaan kegiatan pengabdian ini. Tujuan dari kegiatan ini adalah untuk meningkatkan pengetahuan dan sikap ibu rumah tangga melalui edukasi gizi menggunakan media leaflet gizi seimbang. Kegiatan dilaksanakan pada tanggal 18–19 Juli 2025 dengan jumlah peserta sebanyak 15 ibu rumah tangga. Metode pelaksanaan meliputi sosialisasi, pengisian pre test, penyampaian materi melalui ceramah interaktif menggunakan leaflet, diskusi, dan pengisian post test. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan peserta secara signifikan setelah edukasi diberikan, yang terlihat dari perbandingan skor pre-test dan post test. Rata-rata nilai pengetahuan meningkat dari 4,73 menjadi 7,40 dengan nilai signifikansi p = 0,001. Temuan ini menunjukkan bahwa media leaflet efektif digunakan dalam kegiatan edukasi gizi di wilayah kepulauan yang memiliki keterbatasan akses informasi digital. Edukasi ini tidak hanya meningkatkan pemahaman, tetapi juga mendorong perubahan sikap ke arah perilaku konsumsi gizi seimbang yang lebih baik dalam rumah tangga.   Kata kunci: Gizi Seimbang, Ibu Rumah Tangga, Media Leaflet.